2018
DOI: 10.1186/s12870-018-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of family-1 UDP glycosyltransferases (UGT) and identification of UGT genes for FHB resistance in wheat (Triticum aestivum L.)

Abstract: BackgroundFusarium head blight (FHB), a devastating disease in wheat worldwide, results in yield loses and mycotoxin, such as deoxynivalenol (DON), accumulation in infected grains. DON also facilitates the pathogen colonization and spread of FHB symptoms during disease development. UDP-glycosyltransferase enzymes (UGTs) are known to contribute to detoxification and enhance FHB resistance by glycosylating DON into DON-3-glucoside (D3G) in wheat. However, a comprehensive investigation of wheat (Triticum aestivum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 57 publications
1
87
0
Order By: Relevance
“…Besides the OG and the 17 groups (A–Q) reported in previous analyses (Caputi et al ., ; Stucky et al ., ; Wilson et al ., ), this study identified another UGT group, designated R, that included representatives from seed plants, but not free‐sporing plants (Figure ). The ‘group Q’ from the analysis of Zea mays UGTs (Li et al ., ), ‘group P’ (containing the UGT705 family) from the analysis of T. aestivum UGTs (He et al ., ), and five monocot‐specific UGT families (UGT98, UGT99, UGT702, UGT703 and UGT704) were found to be part of group D in this phylogenomic analysis (Figure ; Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…Besides the OG and the 17 groups (A–Q) reported in previous analyses (Caputi et al ., ; Stucky et al ., ; Wilson et al ., ), this study identified another UGT group, designated R, that included representatives from seed plants, but not free‐sporing plants (Figure ). The ‘group Q’ from the analysis of Zea mays UGTs (Li et al ., ), ‘group P’ (containing the UGT705 family) from the analysis of T. aestivum UGTs (He et al ., ), and five monocot‐specific UGT families (UGT98, UGT99, UGT702, UGT703 and UGT704) were found to be part of group D in this phylogenomic analysis (Figure ; Tables S1 and S2).…”
Section: Resultsmentioning
confidence: 67%
“…Similarly, two group Q UGTs in Musa acuminata (Zingiberales) share an ancestry with the other angiosperm group Q UGTs. However, their homologs are not found in Poales, including Ananas comosus (Bromeliaceae) and O. sativa (Poaceae; this analysis), as well as B. distachyon , S. bicolor , Z. mays and T. aestivum (previous reports), suggesting a loss of group Q UGTs in Poales (Figure ; Caputi et al ., ; Schweiger et al ., ; Li et al ., ; He et al ., ). Functional characterization of group Q UGT homologs from representatives of Malvales (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations